MOTIVATION FOR INDIVIDUALS’ INVOLVEMENT WITH FAN PAGES - Willy Abdillah (Journal of Indonesian Economy and Business (JIEB), 2016)
This research examines the empirical model of individuals’ involvement with fan pages. The research model was developed based on the social influence factors and the brand post popularity model. The research employed an online survey questionnaire. 300 samples were collected by using a purposive sampling technique, and analyzed using the Partial Least Square (PLS) method. The results showed that identification, interactivity, informational content and valence of comment were the motivating factors for the intent to become involved with fan pages. It was indicated that the brand popularity model was not the only relevant model to explain the social computing phenomenon in the context of fan pages, but social influence factors also play a part. The implications for stakeholders and further research are discussed. Keywords: Social influence factors, brand post popularity factors, intention, and involvement with fan pages